Adição de resíduos orgânicos em um argissolo sob sistema agroflorestal no semiárido cearense - Iwata, Bruna de Freitas (2015)
High temperatures, low levels of rainfall, little weathered soils and low phytobiomass production are the main soil and climatic characteristics of the semiarid regions. These factors make the soils of these areas highly vulnerable to loss of quality processes and, consequently, loss of productive potential. In addition, these factors combined with conventionally comprehensive management practices, such as cut and burn agriculture, accelerate soil degradation process. Given the above, land use alternatives such as Agroforestry Systems (AFSs) have been proposed as promoting sustainability in the agricultural land use. To verify the effectiveness of different management systems, carbon has been considered as excellent indicator of soil quality. In this sense, we propose to study the management with the addition of organic waste in a cropping system in alleys and its effects on the carbon fractions, besides the availability of nutrients from such waste. The study was conducted in the municipality of Bela Cruz, semiarid of Ceara. The experimental design was split plot in space, being a 2x4x3 factorial with four replications. In the main plots was studied the fire factor (with fire and without fire); the the subplots studied the addition of organic waste (pruning of legume Gliricidia; pruning of legume Gliricidia and carnauba straw, pruning of gliricídia and biocompound; pruning of legume gliricidia, carnauba straw and biocompound) and the subsubplots studied the depths of soil sampling (0-10, 10-20 and 20-40 cm). The study found that although five years elapsed after preparation with fire there was a greater waste decomposition rate and reduction in the availability of nutrients and organic matter fractions in the alleys managed to burn. Moreover, the fire reduced significantly in both stable and in the fractions of labile organic matter, unlike the effect of the different organic residues, which in conjunction alleys under the management of the waste predominant higher levels of soil nutrients, more basic pH and magazines preserved organic matter, both stable compartments as labile, and higher carbon stocks. It was also observed that the C3 was isotopic reference the common C between residues and these with the C soil of alleys.